Clinically diagnosed tuberculosis and mortality in high burden settings: a systematic review and meta-analysis - Freitag, Benjamin; Sultanli, Ayten; Grilli, Maurizio; Weber, Stefan F.; Gaeddert, Mary; Abdullahi, Osman A.; Denkinger, Claudia M.; Gupta-Wright, Ankur (EClinicalMedicine, 2025)
Background - Clinical diagnosis of tuberculosis (TB), referring to diagnosis without bacteriological confirmation, is common and may affect an individuals’ outcomes. We undertook a systematic review to assess the proportion of people with TB who were diagnosed clinically, and mortality compared to those with bacteriologically confirmation in the published literature. - Methods - We searched Medline, Embase, Web of Science and Cochrane Library from January 2010 to December 2024 using terms for ‘TB’ and diagnostic studies. We excluded studies with participants aged <15 years, not reporting clinical and bacteriologically confirmed TB, not conducted in high TB burden settings, and studies that were not trials, cohort or cross-sectional in design. Published summary data was extracted and risk of bias assessed. Summary estimates for proportion of diagnoses that were clinical were calculated overall and by pre-specified subgroups. Risk ratio for mortality of clinical compared to bacteriological diagnosis was evaluated by random effects meta-analysis. This review was prospectively registered (PROSPERO CRD42023404419). - Findings - Our search identified 5693 records, of which 53 datasets were included. 12 studies were rated as low risk of bias. Median proportion of TB diagnosed clinically (n = 85,623) was 40% (95% CI: 31-46%, interquartile range 27%-53%). The proportion of TB diagnosed clinically was higher in people living with HIV and extrapulmonary TB. Clinical diagnosis did not differ by diagnostic modality available or by study year. The pooled risk ratio for mortality (n = 20,523, 10 studies) was 1·5 (95% CI: 1·0-2·2, I2 = 78·7%) indicating higher mortality in people diagnosed clinically. - Interpretation - Clinical diagnosis of TB remains common and was associated with higher mortality risk than bacteriologically confirmed TB, suggesting conditions other than TB that are not being adequately treated. Better understanding of reasons for clinical TB diagnosis and investment in improved diagnostics for TB and non-TB conditions is needed. - Funding - UK National Institute for Health and Care Research and Academy of Medical Sciences; US National Institutes of Health.